Heterogeneity and viral replication fitness of HSV-1 clinical isolates with mutations in the thymidine kinase and DNA polymerase. (5th September 2022) - Schalkwijk, Hanna Helena; Gillemot, Sarah; Reynders, Marijke; Selleslag, Dominik; Andrei, Graciela; Snoeck, Robert
Abstract: Background: Prolonged antiviral therapy in immunocompromised individuals can result in the emergence of (multi)drug-resistant herpes simplex virus 1 (HSV-1) infections, forming a therapeutic challenge. Objectives: To evaluate spatial and temporal differences in drug resistance of HSV-1 samples from a HSCT recipient and to determine the effect of resistance mutations on viral replication fitness. Patients and methods: Five HSV-1 isolates were recovered from a HSCT recipient who suffered from persistent HSV-1 lesions, consecutively treated with aciclovir, foscarnet, cidofovir and a combination of ganciclovir and cidofovir. Spatial and temporal differences in HSV-1 drug resistance were evaluated genotypically [Sanger sequencing and next-generation sequencing (NGS) of the viral thymidine kinase (TK) and DNA polymerase (DP)] and phenotypically (plaque reduction assay). Viral replication fitness was determined by dual infection competition assays. Results: Rapid evolution to aciclovir and foscarnet resistance was observed due to acquisition of TK (A189V and R222H) and DP (L778M and L802F) mutations. Virus isolates showed heterogeneous populations, spatial virus compartmentalization and minor viral variants in three out of five isolates (detectable by NGS but not by Sanger sequencing). Mutations in the TK and DP genes did not alter replication fitness without drug pressure. TK and/or DP mutants influenced replication fitness under antiviral pressure and showed increased fitness under pressure of the drug they showed resistance to. Conclusions: The use of NGS and dual infection competition assays revealed rapid evolution of HSV-1 drug resistance in a HSCT recipient with spatial and temporal compartmentalization of viral variants that had altered replication fitness under antiviral pressure.